Mobile-Learning Platform for the Development of Entrepreneurial Competences of the Students - Tretyakova, Nataliya; Lyzhin, Anton; Chubarkova, Elena; Uandykova, Mafura; Lukiyanova, Marina (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The aim of the study was to determine the effectiveness of using a mobile learning platform for students’ entrepreneurial competence improvement. The platform was implemented by the Russian State Vocational Pedagogical University and the Financial University under the Government of the Russian Federation. It allowed users to publish assignments, exchange ideas, generate photo and video content, demonstrate creative developments, and receive feedback. The research process enrolled 70 experimental group students, 25 control group students, 2 instructors, and 2 administrators from the considered educational institutions, as well as 3 practitioners invited to review projects. As a result of this examination (Cronbach’s alpha ranged from 0.678 to 0.714), it was noted that 41.4% of all research participants rather agreed that the experiment goals were accomplished and noted personal progress in mastering entrepreneurial competences, whereas 53.4% agreed unequivocally that the experiment was fully successful. Analysis of entrepreneurial competences and deviations from repeated competence evaluations before and after the experiment revealed that the experimental group was marked with notable progress (F (1.32) = 42.26, p = 0.00, = 0.56). Average entrepreneurial competence assessment results for this group were slightly higher than those for control – they constituted 4.5 points against 4.0. Research findings are believed to be universal and interesting to educators and administrative staff of educational institutions or those involved in creating and conducting entrepreneurship training courses.